Real Time Production Monitoring System - Siva Kumar, Subramaniam (2009)
A production monitoring system is a system that is used in real time to record production line problems. It is constructed using programmable logic controller and sensors to collect data from production lines. The real time production monitoring system is designed to collect data automatically and display the data on display boards for the workers to see. Devices in the real time production monitoring system are capable of working as individual units or working together with multiple terminal links such as automated machineries, robotic systems and manual process line. The data will also be relayed to the management for prompt action. Data on production time, non-production time, targets, rejection rates, planned stops, and cycle times will be displayed as well as relayed to the management. Unadulterated data collected from the real time production monitoring system should be relayed to the management without human intervention. Such data would then be interpreted accordingly in order to identify the faults at production level and to spur corrective measures from the management. With the help of this real time production monitoring system the management will be able to monitor both the workers and machine performance. Display of data can also prompt instant action from both workers and line supervisors. The data collected is in line with the requirements of overall equipment effectiveness. Overall equipment effectiveness is the tool for improving efficiency. Efficiency of production lines enables better yield and utilization of the available resources. The real time production monitoring system together with overall equipment effectiveness will help companies to generate higher revenue.